An observational study of incidence and severity of coronary artery disease in peripheral artery disease patients in South India - Chowdekar, Vijay Sai; Peddi, Naveen (International Journal of Research in Medical Sciences, 2020)
Background: There are many studies that have evaluated peripheral artery disease (PAD) using ankle brachial index. However, there is very little epidemiological data on angiographically diagnosed PAD and its association with definite coronary artery disease (CAD) in Indians. The aim of this study is to evaluate the relationship between PAD and CAD in South Indian patients. Methods: This was an observational, descriptive, single-arm, single-centre, retrospective clinical study. The study included 111 patients with known PAD who were admitted to a tertiary care hospital in South India. Patients with PAD by history, clinical examination, and those who underwent peripheral as well as coronary angiography were included in the study. Student t test, chi-square/fisher exact test have been used to find the significance of study parameters. Results: Out of total 111 patients with PAD included in the study, 98 patients were male. 61.1% of patients had co-existing significant CAD and significant PAD. Diabetes was a strong predictor of CAD (p=0.003) and smoking was strongly related to PAD (p=0.028). Elderly patients were associated with occurrence of significant CAD as well as PAD. Conclusions: It can be concluded that there is a definite and significant correlation between PAD and CAD. The elderly population and those at increased risk for atherosclerotic vascular disease have higher liability of PAD; however, PAD is the condition that is mostly under diagnosed and under treated. The awareness about the co-existence of CAD and PAD, and implementation of co-diagnosis in general clinical practice has been poor.